Professionals and Marginals in Slavic and Jewish Cultural Traditions Men - Belova, O. (Academic Studies Press, 2023)
Professionals and Marginals in Slavic and Jewish Cultural Traditions is the annual publication of the Slavic & Jewish Cultures: Dialogue, Similarities, Differences's project for 2022. It includes papers from the international conference of the same name held in Moscow on December 1-3, 2021. The book includes twelve articles by Russian and Israeli scholars who work on the social and cultural role of professionals and marginals in various ethno-confessional traditions. The question of the perception of professionals in culture falls under the opposition "one's own/another's," where belonging to "one's own" or a "foreign community or class" becomes a defining marker. Traditionally, "social strangers," to which representatives of various professions belong, were assigned a special role in calendar, magical, and occasional rites. Thus, professionals and social marginals were not considered outcasts: society assigned them a particular place and role, delegating special cultural functions to them. Like previous publications in this series, Professionals and Marginals in Slavic and Jewish Cultural Traditions is notable for the large amount of field and archival material that it makes publically available for the first time.